Nivel de cumplimiento de aplicación de lista de verificación de seguridad de cirugia en Centro Quirúrgico - Gonzales Crisóstomo, Georgina Paola (2021)
The investigation "Level of compliance with the application of the surgical safety checklist in the Surgical Center" whose objective: To determine the level of compliance with the application of the surgical safety checklist in the Surgical Center of the Víctor Ramos Guardia Hospital - Huaraz. Descriptive, cross-sectional, observational study. Statistical analysis: Cronbach's Alpha Coefficient was used; it is oriented towards the internal consistency of the test. Material and methods: The surgical safety checklist was applied to 92 patients undergoing elective and emergency surgery in a surgical center, carried out by the surgical team. Observing the application of the list in its three phases throughout the intervention process, being recorded in the dichotomous scale instrument to determine compliance. Results: In the 92 patients who underwent surgery in whom the list was applied, it was detected that 44.6% comply with completing each item considered in the three phases. The 55.4% do not comply, generally, because the list is not applied, also, that the times foreseen for each phase are not respected, or that it is completed without being applied, it can also be observed that in the entry phase the 45.7 % comply with the application of the list, in the surgical pause phase 41.3% comply and in the surgical exit phase 26.1% comply. Conclusion: Compliance with the surgery safety checklist application has a low percentage of compliance (44.6%).